2008
DOI: 10.1159/000151439
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Matrix Metalloproteinase-2 Is an Independent Correlate of Proteinuria in Patients with Chronic Kidney Disease

Abstract: Background/Aim:Matrix metalloproteinase-2 (MMP-2) has been implicated in chronic kidney disease (CKD) and cardiovascular disease. However, there is no knowledge about the correlations between serum levels of MMP-2, proteinuria and atherosclerosis in patients with CKD. We investigated whether serum MMP-2 levels were associated with proteinuria, intima media thickness (IMT), and the presence of carotid atherosclerotic plaque in CKD patients. Methods: CKD patients without hemodialysis (n = 99) were enrolled. MMP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 57 publications
1
17
0
1
Order By: Relevance
“…With respect to MMP-2, our data are consistent with previous reports showing that circulating MMP-2 levels are elevated in predialysis CKD 21 and are higher in those with cardiovascular comorbidity. 21,22 MMP-2 levels have also previously been strongly associated with APWV in a hypertensive but otherwise healthy cohort.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With respect to MMP-2, our data are consistent with previous reports showing that circulating MMP-2 levels are elevated in predialysis CKD 21 and are higher in those with cardiovascular comorbidity. 21,22 MMP-2 levels have also previously been strongly associated with APWV in a hypertensive but otherwise healthy cohort.…”
Section: Discussionsupporting
confidence: 92%
“…21,22 MMP-2 levels have also previously been strongly associated with APWV in a hypertensive but otherwise healthy cohort. 23 Similarly, existing data on EDPs indicate a strong correlation with age and history of CVD.…”
Section: Discussionmentioning
confidence: 89%
“…This is in agreement with our previous study, where we observed the association between MMP-2 and IMT, a surrogate marker of CVD in hemodialyzed patients. Recently, Nagano et al [23] also found that serum MMP-2 levels were positively associated with IMT and the presence of atherosclerotic plaque in the carotid artery in non-dialyzed CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 was fond by us to mediate EMT of the tubular epithelial cells downstream of TGF-β [15,16] . A previous report has shown that serum levels of MMP-2 were correlated with proteinuria, intima media thickness and reduced kidney function in patients with CKD [24] . Plasma concentration of MMP-9 was found to be increased in the early stage of diabetic kidney disease [14] .…”
Section: Mmps and Inflammation In Ckdmentioning
confidence: 91%